2018
DOI: 10.1038/s41541-018-0051-y
|View full text |Cite
|
Sign up to set email alerts
|

FIV vaccine with receptor epitopes results in neutralizing antibodies but does not confer resistance to challenge

Abstract: Feline immunodeficiency virus (FIV) is the feline analogue to human immunodeficiency virus (HIV) and utilizes parallel modes of receptor-mediated entry. The FIV surface glycoprotein (SU) is an important target for induction of neutralizing antibodies, and autoantibodies to the FIV binding receptor (CD134) block infection ex vivo; thus highlighting the potential for immunotherapies which utilize anti-receptor antibodies to block viral infection. To determine whether vaccination with CD134-SU complexes could ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 85 publications
0
15
0
Order By: Relevance
“…[ 66 , 67 ] Cross-Infection Enhancement (infection enhancement of one virus by antibodies from another virus) [ 68 , 69 ] Vaccine-associated Virus Interference (where vaccinated individuals may be at increased risk for other respiratory viruses because they do not receive the non-specific immunity associated with natural infection) [ [70] , [71] , [72] , [73] , [74] , [75] ]; Vaccine-Associated Imprinting Reduction (where vaccinations could also reduce the benefits of ‘imprinting’, a protection conferred upon children who experienced infection at an early age) [ 76 , 77 ]; Non-Specific Vaccine Effects on Immune System (where previous infections can alter an individual's susceptibility to unrelated diseases) [ 78 , 79 ]; Impact of Infection Route on Immune System (where immune protection can be influenced by the route of exposure/delivery) [ [80] , [81] , [82] ]; Impact of Combinations of Toxic Stimuli (where people are exposed over their lifetime to myriad toxic stimuli that may impact the influence of any vaccine) [78; 83, 84]; Antigenic Distance Hypothesis (negative interference from prior season’s influenza vaccine (v1) on the current season’s vaccine (v2) protection may occur when the antigenic distance is small between v1 and v2 (v1 ≈ v2) but large between v1 and the current epidemic (e) strain (v1 ≠ e).) [ [85] , [86] , [87] ]; Bystander Activation (activation of T cells specific for an antigen X during an immune response against antigen Y) [ [88] , [89] , [90] ]; Gut Microbiota (Impact of gut microbial composition on vaccine response) [ [91] , [92] , [93] , [94] , [95] ]; Homologous Challenge Infection Enhancement (the strain of challenge virus used in the testing assay is very closely related to the seed virus strain used to produce the vaccine that a subject received) [ [96] , [97] , [98] ]; Immune Evasion (evasion of host response to viral infection) [ …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 66 , 67 ] Cross-Infection Enhancement (infection enhancement of one virus by antibodies from another virus) [ 68 , 69 ] Vaccine-associated Virus Interference (where vaccinated individuals may be at increased risk for other respiratory viruses because they do not receive the non-specific immunity associated with natural infection) [ [70] , [71] , [72] , [73] , [74] , [75] ]; Vaccine-Associated Imprinting Reduction (where vaccinations could also reduce the benefits of ‘imprinting’, a protection conferred upon children who experienced infection at an early age) [ 76 , 77 ]; Non-Specific Vaccine Effects on Immune System (where previous infections can alter an individual's susceptibility to unrelated diseases) [ 78 , 79 ]; Impact of Infection Route on Immune System (where immune protection can be influenced by the route of exposure/delivery) [ [80] , [81] , [82] ]; Impact of Combinations of Toxic Stimuli (where people are exposed over their lifetime to myriad toxic stimuli that may impact the influence of any vaccine) [78; 83, 84]; Antigenic Distance Hypothesis (negative interference from prior season’s influenza vaccine (v1) on the current season’s vaccine (v2) protection may occur when the antigenic distance is small between v1 and v2 (v1 ≈ v2) but large between v1 and the current epidemic (e) strain (v1 ≠ e).) [ [85] , [86] , [87] ]; Bystander Activation (activation of T cells specific for an antigen X during an immune response against antigen Y) [ [88] , [89] , [90] ]; Gut Microbiota (Impact of gut microbial composition on vaccine response) [ [91] , [92] , [93] , [94] , [95] ]; Homologous Challenge Infection Enhancement (the strain of challenge virus used in the testing assay is very closely related to the seed virus strain used to produce the vaccine that a subject received) [ [96] , [97] , [98] ]; Immune Evasion (evasion of host response to viral infection) [ …”
Section: Resultsmentioning
confidence: 99%
“…Homologous Challenge Infection Enhancement (the strain of challenge virus used in the testing assay is very closely related to the seed virus strain used to produce the vaccine that a subject received) [ [96] , [97] , [98] ];…”
Section: Resultsmentioning
confidence: 99%
“…Recombinant p24 protein used for MIA analysis was synthesized as previously described [ 25 ]. MIA was performed using previously established protocols involving conjugation of protein to carboxylated magnetic microspheres (MagPlex ® Microspheres, Luminex, Austin, TX, USA) [ 25 , 26 , 27 ]. Following conjugation, microsphere concentrations were determined by hemocytometer, and protein coupling confirmed by incubation of microspheres with phycoerythrin (PE)-conjugated detection antibodies [ 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…Twelve (12) SPF cats from the Andrea D. Lauerman Specific Pathogen Free Feline Research Colony (Fort Collins, CO, USA) were housed as previously described above in accordance with CSU IACUC-approved protocols and were acclimated to the facility for 2 weeks prior to initiation of the study. As part of an FIV vaccination protocol [41], animals were intravenously inoculated with 75,000 infectious units of FIV PPR (1 mL of a viral stock solution with a TCID 50 titer of 1 × 10 5.87 ) at 8–11 weeks of age. At the onset of this study, all animals were between 43–46 weeks of age and were confirmed to be FIV-positive by quantitative PCR detection of viral RNA [41].…”
Section: Methodsmentioning
confidence: 99%
“…As part of an FIV vaccination protocol [41], animals were intravenously inoculated with 75,000 infectious units of FIV PPR (1 mL of a viral stock solution with a TCID 50 titer of 1 × 10 5.87 ) at 8–11 weeks of age. At the onset of this study, all animals were between 43–46 weeks of age and were confirmed to be FIV-positive by quantitative PCR detection of viral RNA [41].…”
Section: Methodsmentioning
confidence: 99%